Study on the Mechanism of Thermal Expansion Injury of Hepatocyte Microspheres during Cryopreservation - Yu Zengying; Liu Baolin (Zhileng xuebao)
In the cryopreservation of monolayer adherent cells, the detachment of cells from the substrate is one of the main factors that influence the effect of cryopreserved cells. The main reason for this type of shedding is the difference in the coefficient of thermal expansion (CTE) of the matrix and cells. The cooling rate and final temperature are both factors that cause a change in the CTE. In this study, the cryopreservation plan was compared and screened when the difference in thermal expansion was the smallest. The effect of thermal expansion damage on the cryopreservation of hepatocyte complexes was explored by measuring the CTE of hepatocytes and microcarriers during the slow freezing process (cooling rate was 1 ℃/min, 2 ℃/min, and 5 ℃/min, and the final temperature of was -30 ℃. The final experiment concluded that when the cooling rate was 1 ℃/min, the thermal expansion difference between hepatocytes and microcarriers was the smallest, and the cryopreservation effect of the corresponding composite was the best, with survival and adhesion rates of 62.66%±0.67% and 37.2%±1.25%, respectively. Thermal expansion damage between cells and microcarriers exists throughout the cooling process and is one of the main factors affecting the cryopreservation effect of liver cell complexes.